Effects of surfactant and ionic concentration on properties of dual physical crosslinking self-healing hydrogels by hydrophobic association and ionic interactions. (25th February 2020) - Li, Yayu; Zhou, Tianyang; Yu, Zhangyong; Wang, Fei; Shi, Dongjian; Ni, Zhongbin; Chen, Mingqing
Abstract : Two kinds of dual crosslinking hydrogels have adjustable mechanical properties, self-healing and self-recovery performances. Abstract : Dual crosslinking network hydrogels fabricated by non-covalent interactions can have both excellent mechanical properties and tolerable self-healing performances. Although a range of hydrogels that are constructed by hydrophobic association-interaction (HAI) or/and Fe(iii ) ionic interactions have been reported, as far as we know, there has been little progress in the case of influence due to surfactant types and Fe(iii ) contents on the mechanical and self-healing properties. In this study, two kinds of dual crosslinking hydrogels based on acrylic acid (AA) and stearyl methacrylate (SMA) were fabricated by using sodium dodecyl sulfate (SDS) and polyvinyl alcohol (PVA) as physical crosslinking points, respectively, in which PAA was used as the hydrophilic part and PSMA as the hydrophobic part, and the ionic interaction of Fe(iii ) (Fe 3+ ) ions combined carboxylic groups (–COO − ) of PAA as the second crosslinking point. Mechanical properties, self-healing and self-recovery performances of the prepared hydrogels and their influencing factors were investigated. The mechanical properties of the two hydrogels increased with higher Fe 3+ contents and reached a maximum at 0.3 mol% of Fe 3+, while they increased gradually with the AA contents. The hydrogels showed self-healing properties with recoverable mechanical values after healing for 24 h. Moreover, the hydrogels also showed around 90% of self-recovery properties. The hydrogels formed by using PVA as a surfactant (HPAA-Fe 3+ @PVA) showed higher mechanical properties, but lower self-healing and self-recovery efficiencies, compared with those of the SDS-associated hydrogels (HPAA-Fe 3+ @SDS), because the PVA macromolecules with longer chains increased the chain entanglement. These results indicate that the mechanical properties, self-healing and self-recovery performances can be regulated by changing the surfactant types and compositions of the AA and Fe 3+ of the hydrogels.